Endodontic Treatment of Chronic Apical Periodontitis with The Drug Hydroxy calcium by Delayed Filling - Muratova Saodat Kadirovna; Naimov Sadridin Sirozhitdin ugli; Toshtemirov Islom Chori ugli (Genius Journals, 2023)
Treatment of patients with chronic periodontitis is one of the most difficult and important tasks of modern dentistry. 134 patients were examined on an outpatient basis with endodontic treatment of the two most common types of pastes: resorcinol-formalin and Calcevit. According to the type of paste, all examined patients were divided into two groups: 78 patients (51.5%) whose teeth were sealed with resorcinol-formalin paste and 56 patients (48.5%) with Calcite paste. According to the results of the study, it was found that in the group of teeth previously treated with resorcinol-formalin paste, more than 2/3 were molars (77.0 + 2.2%), every fifth tooth was premolar (19.1 + 2.0%) and there were fewer front teeth (3.9 + 1.0%). In the group of teeth previously treated with Calcite paste, the ratio of types of teeth in different age subgroups differed. Almost equal proportions in frequency were noted for the anterior teeth (29.2 + 2.4%), premolars (29.8 + 2.4%), the proportion of molars was slightly higher (41.0 + 2.4%).
Keywords: Calcite paste; resorcinol-formalin paste; radiological